2018
DOI: 10.1088/1741-2552/aad840
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic interrogation of neurovascular coupling in the cerebral cortex of transgenic mice

Abstract: The proposed approach opens new lines of research with potential applications in understanding the role of different cell types in the cerebrovascular regulatory mechanisms and the study of the adaptive process of angiogenesis in the cerebral cortex. The observation of incoherent responses of vessel diameter, blood flow-rate, and velocity suggests that such detailed information is necessary to obtain an accurate interpretation of the data acquired via hemodynamic based functional imaging techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
(82 reference statements)
1
12
0
Order By: Relevance
“…Although the dominant view is that blood pulsatility gets dampened before it reaches the microvasculature (O'Rourke and Safar, 2005), recent measurements have challenged this view. Indeed, significant pressure and velocity oscillations have been reported in capillaries down to 4 µm in diameter (Gu et al, 2018;Gurov et al, 2018;Koutsiaris, 2016), and 40-µm-diameter mouse brain arterioles have been shown to exhibit 10% strain at the heartbeat frequency, demonstrating that the pulse penetrates deep into the microvasculature (Atry et al, 2018).…”
Section: Forces Exerted On Pericytesmentioning
confidence: 99%
“…Although the dominant view is that blood pulsatility gets dampened before it reaches the microvasculature (O'Rourke and Safar, 2005), recent measurements have challenged this view. Indeed, significant pressure and velocity oscillations have been reported in capillaries down to 4 µm in diameter (Gu et al, 2018;Gurov et al, 2018;Koutsiaris, 2016), and 40-µm-diameter mouse brain arterioles have been shown to exhibit 10% strain at the heartbeat frequency, demonstrating that the pulse penetrates deep into the microvasculature (Atry et al, 2018).…”
Section: Forces Exerted On Pericytesmentioning
confidence: 99%
“…Importantly, these mechanical forces are highly dynamic due to blood flow pulsatility. Although pulsatility has traditionally been assumed to be completely dampened by the time blood reaches the microvasculature, recent data challenge this consensus and have reported significant velocity and diameter oscillations even in the smallest capillaries [18][19][20][21][22]. Interestingly, in diseases such as hypertension, the higher pulse pressure penetrates deeper into the vascular tree, further increasing pulsatility in the microvasculature [7,23].…”
Section: Introductionmentioning
confidence: 99%
“…Optogenetics, an advanced method for cell-type-specific manipulation, has been applied to understanding the mechanism of neurovascular coupling. For example, optogenetic neuronal excitation was shown to induce vasodilation (Atry et al, 2018;Krawchuk et al, 2020;Mester et al, 2019;Uhlirova et al, 2016), which was accompanied by an intracellular Ca 2+ decrease in blood vessel cells (Hill et al, 2015). In addition, optogenetic astrocytic activation was shown to increase CBF independent of neural activation (Masamoto et al, 2015;Takata et al, 2018).…”
Section: Introductionmentioning
confidence: 99%